A Parsec-scale Catalog of Molecular Clouds in the Solar Neighborhood Based on 3D Dust Mapping: Implications for the Mass–Size Relation - Shlomo Cahlon; Catherine Zucker; Alyssa Goodman; Charles Lada; João Alves (The Astrophysical Journal, 2024)
We dendrogram the Leike et al. 3D dust map, leveraging its ∼1 pc spatial resolution to produce a uniform catalog of molecular clouds in the solar neighborhood. Using accurate distances, we measure the properties of 65 clouds in true 3D space, eliminating much of the uncertainty in mass, size, and density. Clouds in the catalog contain a total of 1.1 × 10 ^5 M _☉ , span distances of 116−440 pc, and include a dozen well-studied clouds in the literature. In addition to deriving cloud properties in 3D volume density space, we create 2D dust extinction maps from the 3D data by projecting the 3D clouds onto a 2D “Sky” view. We measure the properties of the 2D clouds separately from the 3D clouds. We compare the scaling relation between the masses and sizes of clouds following Larson. We find that our 2D projected mass–size relation, M ∝ r ^2.1 , agrees with Larson's Third Relation, but our 3D derived properties lead to a scaling relation of about one order larger: M ∝ r ^2.9 . Validating predictions from theory and numerical simulations, our results indicate that the mass–size relation is sensitive to whether column or volume density is used to define clouds, since mass scales with area in 2D ( M ∝ r ^2 ) and with volume in 3D ( M ∝ r ^3 ). Our results imply a roughly constant column and volume density in 2D and 3D, respectively, for molecular clouds, as would be expected for clouds where the lower density, larger volume-filling gas dominates the cloud mass budget.